Simulation of the Separation of Homogeneous Whole Blood in a Spin-up Rotating Cylindrical Container - J. S. Fan; L. L. Xiao; C. S. Lin; P. Wei; K. X. Zhang (Journal of Applied Fluid Mechanics)
Centrifugal separation is a highly efficient technique for accelerating the sedimentation of blood constituents in a cylindrical container through high-speed spin-up rotation. Few studies have reported on the separation of different blood constituents from homogeneous mixture of whole blood. In this study, the process through which blood constituent sedimentation occurs in a spin-up rotating cylindrical container is numerically investigated. Whole blood is considered a homogeneous mixture of red blood cells (RBC) and plasma, which are both considered incompressible viscous liquids. The Euler multi-fluid VOF (volume of fluid) model is introduced to simulate the separation of RBCs and plasma. The effects of the rotation speed and the geometric construction of the cylindrical container on the sedimentation and stratification of different blood constituents are studied. A stable interface between the RBC layer and plasma layer forms earlier in a high position. With an increase in the rotation speed, the interface between the RBCs and plasma layers forms more quickly. In the cylindrical container with a helical groove on the outer wall, a stable vortex occurs near the groove, which forces red blood cells to move toward the lower location of the groove, resulting in a conical distribution of the RBC layer and a larger volume fraction of plasma near the exit at the top. This allows for sufficient precipitation of the plasma, improving the separation efficiency.